PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2011-2015) - Imas Hening Hikmahwati, 13.05.52.0147; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aims to examine the effect of financial performance, firm size and corporate governance on the disclosure of sustainability report on mining companies in Indonesia stock exchange. The population of this study is a mining company listed on the Indonesian Stock Exchange (BEI) during 2011-2015 reporting sustainability report. The samples included in this research criteria were 35 companies using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis with SPSS program 19. The result of the research shows that profitability and liquidity variables have a significant positive effect on sustainability report disclosure, firm size has significant negative effect to sustainability report disclosure, while audit committee, board of directors, and independent board of commissioner have no effect on sustainability report disclosure.Keywords: Disclosure of Sustainability Report, Profitability, Company Size, Audit Committee, Board of Directors, and Independent Board of Commissioners